1973
DOI: 10.1161/01.res.32.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Normal Myocardial Function and Energetics in Volume-Overload Hypertrophy in the Cat

Abstract: Depressed contractility with a paradoxically increased myocardial oxygen consumption has been associated with pressure-overload hypertrophy. The present experiments investigated myocardial hypertrophy induced by volume overload. Right ventricular volume overload was produced in 19 cats by surgically creating atrial septal defects (ASD); these cats were compared with 10 sham-operated control cats. The ASD cats showed an increase in the ratio of pulmonary blood flow to systemic blood flow from 1.04 ± 0.01 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 30 publications
4
22
0
1
Order By: Relevance
“…Volume overload hypertrophy of the feline RV was created as before (20) by creating an atrial septal defect (ASD) via the BlalockHanlon procedure (21). The normally loaded left ventricle (LV) served as a same-animal control in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…Volume overload hypertrophy of the feline RV was created as before (20) by creating an atrial septal defect (ASD) via the BlalockHanlon procedure (21). The normally loaded left ventricle (LV) served as a same-animal control in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…In direct contrast to data for dogs subjected to aortic stenosis, colchicine caused a clear decrease in LV contractility (1-2 and 4) it must then be found in that infected animal. Thus, in the initial study of cardiocytes from the pressure-overloaded feline RV (29), controls consisted of nonhypertrophied cardiocytes from the normally loaded LV from the same animal and equivalently hypertrophied cardiocytes from the volume-overloaded feline RV, which was known to exhibit normal contractile function (5). In neither control were the linked cytoskeletal and contractile defects present.…”
Section: Is There a Specific Link Between Microtubule Network Densitymentioning
confidence: 99%
“…Thus, the depression of contractile state observed in these studies may have resulted from examination of muscles before sufficient time had elapsed for complete recovery of function. Also, it has been clearly demonstrated that contractile state of myocardium hypertrophied by volume loading is normal (11,12), further suggesting that contractile state is more closely related to the conditions producing hypertrophy than to the increase in muscle mass per se.…”
Section: Introductionmentioning
confidence: 99%